A CROSS-SECTIONAL STUDY ON TECHNIQUE FOR REMOVAL OF EAR OSSICLES: A DIAGONAL CORONAL SECTION METHOD. - Sodhi, Shubhpreet; Bhavna; Santram, Khayati (Student's Journal of Health Research Africa, 2024)
Background The retrieval of intact ear ossicles (malleus, incus, and stapes) from the temporal bone is crucial for anatomical studies, implant design, and educational purposes. Previous techniques have been laborious, destructive, and required advanced equipment, making the process challenging, especially for the fragile stapes. The present study is undertaken to retrieve the ossicles intact from the temporal bone to measure the various parameters of these ossicles in the North Indian population for designing and constructing the implants. Methods A cross-sectional study was conducted on 50 male and 50 female cadavers from North India. A diagonal coronal section technique was employed to retrieve 200 ear ossicles from temporal bones, aiming for a minimally destructive approach. This technique allowed precise extraction with less damage than traditional methods, particularly beneficial for preserving the delicate structure of the stapes. Results The diagonal coronal section method successfully extracted complete ossicle sets with minimal damage. The study verified that this technique is effective and reliable for intact ossicle retrieval, enhancing anatomical understanding and aiding in implant development for the North Indian population. Conclusion This approach is less destructive and allows for easy retrieval of ear ossicles. The technique is highly reliable and preserves the anatomical integrity of these bones, especially the fragile stapes, making it suitable for educational and research applications. Recommendation The diagonal coronal section method is recommended as a standard procedure for extracting ear ossicles. It is instrumental in both educational settings for medical students and in research for developing otological implants.